Fenomena Fear of Missing Out (FoMO) pada Mahasiswa Pendidikan Sosiologi Universitas Negeri Makassar - Rezkia Yusuf; Alyah Arina; Muhammad Syukur; M. Ridwan Said Ahmad; Muh. Samhi Mu’awwan A. M. (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The progress of information and communication technology is very fast. This has an impact on the line of human life, especially the post-millennial generation. Entering the era of society 5.0, students are part of the post-millennial generation. Where the level of use of social media on Students increases. The development of technology always goes hand in hand with negative impacts, social media is currently not only used as a tool to obtain information, but is used as a means to spend time and even follow the lives and activities of other people. Thus creating fear, anxiety about being left behind by news which makes individuals an uncontrollable desire to continue to be connected with the activities of other people on social media. This phenomenon is called fear of missing out (FoMO). This research method uses descriptive qualitative research. With the subject of Sociology Education students at Makassar State University. In the process of collecting data is done by interview.